Learning Designs for the Addition and Subtraction of Two-Digit Numbers based on Realistic Mathematics Education Principles Using Snakes and Ladders Game - Irfan Fauzi; Rohma Mauhibah; Al Jupri (IAIN Syekh Nurjati Cirebon, 2021)
Abstract Students have difficulties in understanding addition and subtraction of numbers. These difficulties need to be anticipated in order to find ways to reduce them. This research aims to develop the learning designs for addition and subtraction of two-digit numbers using the Realistic Mathematics Education (RME) approach. The snakes and ladders game was used as the learning media, while the language of arrows was used as the context of learning. Using educational design research, this study involved a total of 29 first graders of one of the elementary schools in Bandung City, Indonesia. The sample in this study was selected using purposive sampling. The data were collected through tests and observations. The results of this research indicated that the learning designs had a positive impact on the students’ understanding of the addition and subtraction of two-digit numbers. The students' average score after learning the addition and subtraction of two-digit numbers was 70.62. The principles of Realistic Mathematics Education (RME) are the key to student success in understanding mathematical concepts. This research could be used as a reference for developing mathematics learning designs using the RME approach in elementary schools.Keywords: learning designs, addition and subtraction of numbers, realistic mathematics education.Abstrak Siswa mengalami kesulitan dalam memahami penjumlahan dan pengurangan bilangan. Kesulitan-kesulitan tersebut perlu diantisipasi agar dapat ditemukan cara untuk menguranginya. Penelitian ini bertujuan untuk mengembangkan desain pembelajaran penjumlahan dan pengurangan bilangan dua digit dengan menggunakan pendekatan Realistic Mathematics Education (RME). Permainan ular tangga digunakan sebagai media pembelajaran, sedangkan bahasa panah digunakan sebagai konteks pembelajaran. Menggunakan educational design research, penelitian ini melibatkan total 29 siswa kelas satu salah satu sekolah dasar di Kota Bandung, Indonesia. Sampel dalam penelitian ini dipilih dengan menggunakan purposive sampling. Pengumpulan data dilakukan melalui tes dan observasi. Hasil penelitian ini menunjukkan bahwa desain pembelajaran berpengaruh positif terhadap pemahaman siswa tentang penjumlahan dan pengurangan bilangan dua angka. Nilai rata-rata siswa setelah mempelajari penjumlahan dan pengurangan bilangan dua angka adalah 70,62. Prinsip-prinsip Realistic Mathematics Education (RME) menjadi kunci keberhasilan siswa dalam memahami konsep matematika. Penelitian ini dapat dijadikan acuan untuk mengembangkan desain pembelajaran matematika dengan pendekatan RME di sekolah dasar.Keywords: desain pembelajaran, penjumlahan dan pengurangan bilangan, realistic mathematics education.